Selection of "Selection" Sources from Harvesting Varieties According to Hills Conditions - Khalilov Kh. R; Bobaeva A. S.; Khalilov Sh. Kh. (International Journal on Orange Technologies, 2022)
The article describes the feasibility of selecting promising sources of selection of grassland forage species suitable for hills and their use in the phytomelioration of hill pastures.